Biological effects of tourmaline treatment on Dehalococcoides spp. during the reductive dechlorination of trichloroethylene. Issue 20 (25th March 2021) - Li, Tielong; Wen, Jiaxin; Li, Bingjie; Ding, Shihu; Wang, Wei
Abstract : To explore the application of mineral in bioremediation of contaminated aquifers, this study investigated tourmaline-induced changes in TCE degradation, community structure, cell proliferation and gene expression of dechlorinating bacteria. Abstract : In the present study, to develop the application of biostimulation for the in situ remediation of trichloroethylene (TCE) in contaminated groundwater/soil, a mixed culture containing Dehalococcoides spp. was employed to investigate the biological effects of the polarized mineral tourmaline on the dechlorination performance, community structure, cell proliferation and expression of two model gene ( tceA and vcrA ) coding for reductive dehalogenases (Rdase). It was observed that tourmaline could speed up the biological dechlorination of TCE by promoting the growth and metabolism of the bacteria, impacting the expression of RDase genes. Compared with the bacteria system, the time for the complete removal of TCE was reduced from 7 d to 4 d when 5 g L −1 tourmaline was added to the bacterial system, and the yield of the innocuous product ethene increased from 53% to 91% on the 15th day of reaction. At this time, the community similarity of the tourmaline-added bacteria system and the bacteria system was 83.1%. The Dehalococcoides spp. in the tourmaline system grew 2 times more than that in the bacteria system. Moreover, an increase in the expression levels and decrease in the relative expression ratios of the functional genes ( tceA and vcrA ) were observed with the addition of tourmaline. The above analysis provides a molecular basis for the investigation of the biostimulation process by minerals.